Teachers’ readiness in the implementation of online learning during COVID-19 pandemic - Islamiani Safitri; Ika Chastanti; Lily Rohanita Hasibuan; Irmayanti Irmayanti; Sujarwo Sujarwo; Rohana Rohana; Hamni Fadlilah Nasution (Institute of Advanced Engineering and Science, 2022)
This research investigated teachers’ readiness in implementing online learning during COVID-19 pandemic. This was quantitative research with a description analysis approach. The data collection technique used a structured questionnaire. It involved 78 senior high school teachers as respondents spread across nine sub-districts in Labuhanbatu Regency, Indonesia. The results revealed that the implementation of online learning has not been maximized. There are several factors that influence science teachers in running online learning, including the readiness of teachers to use various platforms as online learning media has not varied, the quality of the internet network is poor in some areas, some students do not have a smartphone/computer and have difficulty in buying internet data packages. The results of this study are expected to be used as an evaluation material to improve the online learning system to make it more effective and efficient.